Meningkatkan Kemampuan Membaca Permulaan Pada Anak Kelompok A Melalui Media Buku Aktif Pop Up di TK Hidayatus Shibyan - Kayatin, Widya Nur; Khotimah, Nurul; Maureen, Irena Yolanita (STAI Denpasar Bali, 2023)
This research aims to find a solution to the problem of difficulties in improving language skills in terms of early reading in early childhood in group A1 in Hidayatus Shibyan Surabaya. The research method used in this research is the research and development method or often called Research and Development (R&D). The subjects of this research are students in group A1 of the Hidayatus Shubiyan Kindergarten for the 2023-2024 academic year with a total of 15 students with an average age 4-5 years old, consisting of 9 female students and 6 male students. The results of the research presented data on the differences between the use of Pop Up learning media and increasing initial reading abilities in the A1 group of Kindergarten Hidayatus Shibyan Surabaya. From the table above, the result is tcount = - with a significance level of 0.000. Because the significance level is smaller than 0.05, Ha is accepted, and Ho is rejected. Based on the results of this research, it can be concluded that